Corporate-level strategy and firm performance: evidence from China. Issue 1 (18th March 2019) - Li, Boya; Chen, Shou
Abstract : Purpose: The research interest in this paper is primarily in the question of how important changes in corporate-level strategy affect firm performance. This paper aims to explore the relationship between strategic change and performance, illustrate the frequency patterns of major strategic changes and assess the multi-period performance implications of major strategic changes. Design/methodology/approach: This paper defines strategic change by combining contingency theory and resource-based view. The panel data from 1973 listed firms of China's A-share market that reported data between the years 2004 and 2015 are selected as the sample to test various relationships and effects between performance and strategic change. Findings: This paper empirically shows that change in strategies benefits subsequent firm performance, specifically resources re-allocation among existing businesses will result better performance, and successful firms exhibit less strategic change than those performing poorly. It also demonstrates that, in China, the effects of a major strategic change on subsequent performance peaks after one year, but starts to decline thereafter. Originality/value: This paper explores whether changes, especially important changes, in corporate-level strategy influence subsequent firm performance, and illustrates how frequently a listed firm in China makes decisions about corporate-level strategy. It contributes empirically to the literature by providing one of the first empirical evidence on assessing the effects of important changes in corporate-level strategy on performance.